Project feasibility of clean development mechanism in Colombia - Restrepo Giraldo, Jaime Andres (Visión electrónica, 2014)
This paper presents the results of investigation of the likelihood that the Kyoto Protocol provides for the development of projects of the Clean Development Mechanism, CDM forestry, river basin Ot´un, Risaralda department, Colombia. It also analyzes the feasibility of implementation in this area consists of several national parks and protected areas for wildlife, likewise, the investigation establishes what are the potential risk factors (political, economic or technical) in the implementation of CDM projects and proposes guidelines for administration. The study concludes and recommends that these projects may well go ahead and be successful if clear policies by the State, if it has the support of environmental NGOs and if, fundamentally, is achieved by the active participation of local communities in the definition and ongoing assessment.